2013
DOI: 10.1371/journal.pone.0081924
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Replacing Sugar with Non-Caloric Sweeteners in Beverages on the Reward Value after Repeated Exposure

Abstract: BackgroundThe reward value of food is partly dependent on learned associations. It is not yet known whether replacing sugar with non-caloric sweeteners in food is affecting long-term acceptance. ObjectiveTo determine the effect of replacing sugar with non-caloric sweeteners in a nutrient-empty drink (soft drink) versus nutrient-rich drink (yoghurt drink) on reward value after repeated exposure. DesignWe used a randomized crossover design whereby forty subjects (15 men, 25 women) with a mean±SD age of 21±2 y an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 37 publications
(43 reference statements)
0
37
0
Order By: Relevance
“…Contrary to these findings, a recent clinical trial reported that repeated consumption of NNS- and sucrose-sweetened versions of a drink did not alter the reward value of either version [120]. In this study, subjects consumed fixed portions of sucrose- and NNS-sweetened versions of a beverage that were distinguishable by means of colored labels.…”
Section: Extra-oral Mechanismsmentioning
confidence: 56%
“…Contrary to these findings, a recent clinical trial reported that repeated consumption of NNS- and sucrose-sweetened versions of a drink did not alter the reward value of either version [120]. In this study, subjects consumed fixed portions of sucrose- and NNS-sweetened versions of a beverage that were distinguishable by means of colored labels.…”
Section: Extra-oral Mechanismsmentioning
confidence: 56%
“…This has been tested in rodents where no evidence of extinction was noted after 10 trials with saccharin stimulation [27]. In humans, ingestion of beverages with sucralose, sucralose plus acesulfame-K or sucrose 10 times revealed no evidence that it altered their reward values [96]. The present study sought to further evaluate this question and failed to note a differential response to repeated exposure to a low calorie versus a nutritive sweetener.…”
Section: Discussionmentioning
confidence: 95%
“…Is the response to a lowcalorie beverage with artificial sweeteners the same after repeated exposure, or do people slowly learn that "diet" product contain less calories? For this case, in which there is no deprivation, it is quite hard to demonstrate such dietary learning [78] although there is some evidence for detection of calories in the mouth [79,80]. Another important consideration is whether it makes a difference whether one goes from, for example, 200 50 kcal, or from 150 0 kcal.…”
Section: How Physiological Psychological and Emotional Factors Predmentioning
confidence: 98%